(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article is devoted to the development of international financial relations in the context of the globalization of financial relations, and in the future, ways to develop mutual relations with international financial organizations and effectively use foreign investments are presented.